Implementation Scattergories Game To Improve Vocabulary Skill Of Students’ In Junior High School Yayasan Perguruan Keluarga - Ridwin Purba; Marhaeni Kartika Dewi Matondang; Putri Aprilidya Sinaga (Bilingual : Jurnal Pendidikan Bahasa Inggris, 2023)
The objective of this research is intended to answer the problem about the Scattergories game is improve or not improve the students vocabulary skills at the seventh one (VII-1) grade students of SMP Yayasan Perguruan Keluarga Pematang Siantar. This research was conducted at SMP Yayasan Perguruan Keluarga Pematang Siantar. This research used quantitative with true experimental method. Population of this research was grade seventh with 2 classes which consists 61 students and the sample of this research was 30 students in one class. The technique of collecting data was pre-test and post-test. The technique of analyzing data by using some formulas. The result of the research was the mean score is 14 the standard deviation is 71 ttest of research (9,10) with the significant difference is 0,19. It means that H0 is rejected and Hais accepted. Using Scattergories game to improve vocabulary skillthe students in seventh grade of SMP Yayasan Perguruan Keluarga Pematang Siantar. It can be concluded that teaching vocabulary with Scattergories game make the students more active in playing the game make the students more motivated and easier to understand and get the lesson